Phytochemical screening and evaluation of analgesic, anti-inflammatory activities of Peganum harmala Linn., seeds in rodents - M. R. Pradeep Kumar , Shrinivas D. Joshi, V. H. Kulkarni, Chetan Savant (Journal of Applied Pharmaceutical Science, 2015)
The objective of this research work is to carryout the phytochemical screening and evaluate the analgesic, anti-inflammatory activities of Peganum harmala Linn., seeds. In this study different extracts of Peganum harmala (Linn) seeds were evaluated for analgesic and anti-inflammatory activities using glacial acetic acid induced writhing and carrageenan induced rat paw edema models respectively. For analgesic and anti-inflammatory activities aspirin and diclofenac were used as standard drugs respectively. The ethyl acetate extract showed significant analgesic and anti-inflammatory activities, thus it can be considered as a potential candidate for analgesic and antiinflammatory activities. The presence of alkaloids, steroids, flavonoids in ethyl acetate extract of Peganum harmala (Linn) seeds could be attributed for the claimed analgesic and anti-inflammatory activities.
Keywords: Peganum harmala, Zygophyllaceae, analgesic, anti-inflammatory, carrageenan.